1993
DOI: 10.1016/0035-9203(93)90434-r
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of mefloquine resistance with penfluridol in isolates of Plasmodium falciparum from south-west Nigeria

Abstract: The susceptibilities of isolates of Plasmodium falciparum from Nigeria and two reference cloned strains (D6 and W2) to mefloquine or chloroquine alone and in combination with either penfluridol, a piperidine analogue, or verapamil were determined using a modification of the semiautomated microdilution technique. Six of the isolates showed reduced susceptibility to mefloquine in vitro. The response of the 6 isolates was similar to that of the mefloquine resistant reference clone D6, with 50% inhibitory concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…In contrast to verapamil, penfluridol shows no effect on CQ sensitivity. 33 The mechanistic basis for the effects seen with penfluridol, the reasons it is not effective in all isolates exhibiting reduced susceptibility, and the clinical relevance remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to verapamil, penfluridol shows no effect on CQ sensitivity. 33 The mechanistic basis for the effects seen with penfluridol, the reasons it is not effective in all isolates exhibiting reduced susceptibility, and the clinical relevance remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to antimalarial drugs (CQ, QN, MQ, and HF) in the presence and absence of fixed concentration of chemosensitizers (verapamil [5 M] was used as an agent that can reverse resistance to CQ and QN while penfluridol [1 M] was used as an agent reported to selectively enhance sensitivity to MQ in resistant isolates of P. falciparum 33 ) were determined by measurement of 3 H-hypoxanthine incorporation into parasite nucleic acids as previously described. 34 The concentration of drug that inhibits parasite growth by 50% (IC 50 ) was determined from the log dose/response relationship as fitted by GRAFIT (Erithacus Software, Kent, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…For purposes of interpretation, when RMI is Ϸ1, there is no change in antimalarial activity, whereas an RMI of Ͻ Ͻ1 represents potentiation of antimalarial activity (i.e., evidence of synergy) and an RMI of Ͼ Ͼ1 represents antagonism (62).…”
Section: Methodsmentioning
confidence: 99%
“…To know if the synergistic association of ellagic acid with chloroquine and mefloquine was not due to a chloroquine-and mefloquine-resistant reversion effect, a chloroquine-resistant reversion test was carried out as a positive control using verapamil hydrochloride (Sigma, France) on chloroquine-resistant strain W2-Indochina (IC 50 for chloroquine of 300 nM) and on chloroquine-sensitive strain F32- Tanzania (IC 50 for chloroquine of 30 Ϯ 2 nM) according to the experimental procedures described previously by Martin et al (16). For a mefloquine resistance reversion assay, the positive control consisted of using penfluridol (Sigma, France) (17,18), a piperidine analogue, and Plasmodium falciparum strains FcM29-Cameroon, sensitive to mefloquine (IC 50 of 7 Ϯ 4 nM), and Dd2, which showed a reduced susceptibility to mefloquine in vitro (IC 50 of 21 Ϯ 3 nM). Amplification assays of the P. falciparum MDR1 gene on strains Dd2 and FcM29 confirmed that Dd2 showed a reduced susceptibility to mefloquine by expressing an average of three copies, compared with reference strain FcM29, which expressed only one copy (data not shown).…”
Section: Methodsmentioning
confidence: 99%